Kajian Al-Qur’an Pendekatan Sosiologis: Lingkungan dan Kewajiban Manusia dalam Al-Qur’an: Qur'an Studies Sociological Approach: Environment and Human Obligations in the Qur'an - Burhanudin Al-Ghoni; Satria Putra, Dede; Fathurohman, Wahid; Kamal, Iflahul; Faiq Al Ghifari, Muhammad; Nurrohim, Ahmad (DIRASAH: Jurnal Kajian Islam, 2025)
This research elaborates on the Islamic view of human interaction with the environment based on Qur'anic verses related to human duties and functions. This issue is vital amid accusations that religion and human perspective are one of the roots of various ecological crises. The research method used is a descriptive qualitative method. By describing verses that discuss human functions and duties and verses related to the environment, this study shows that Islam comprehensively views the relationship between humans and the environment. The results of the survey show that Islam views humans and nature as an interdependent unit, with the obligation to maintain balance as a manifestation of the faith of a servant as 'Abdullah and the caliph on earth.